Allopurinol and the risk of incident peripheral arterial disease in the elderly: a US Medicare claims data study. (3rd July 2017) - Singh, Jasvinder A; Cleveland, John
Abstract: Objective: The aim was to examine whether allopurinol use is independently associated with a reduction in the risk of incident peripheral arterial disease (PAD) in the US elderly. Methods: We used the 5% random Medicare sample from 2006 to 2012 to examine the association of allopurinol use and duration of use with the risk or hazard of incident PAD in a retrospective cohort study using a new user design. Multivariable Cox regression models adjusted for demographics, co-morbidity, cardiac medications and cardiac conditions. Hazard ratios (HRs) and 95% CIs were calculated. Results: We identified 26 985 episodes of incident allopurinol use in 25 282 beneficiaries; 3167 allopurinol use episodes (12%) ended in incident PAD. In multivariable-adjusted analyses, allopurinol use was associated with an HR of 0.88 (95% CI: 0.81, 0.95) for incident PAD, as was female gender, HR 0.84 (95% CI: 0.78, 0.90). In a separate multivariable-adjusted model, compared with no allopurinol use, longer durations of allopurinol use were associated with lower HR of PAD: 181 days to 2 years, 0.88 (95% CI: 0.79, 0.97); and >2 years, 0.75 (95% CI: 0.63, 0.89). Other factors significantly associated with a higher HR of PAD were age 75 to < 85 and ⩾85 years, higher Charlson index score and black race. Sensitivity analyses that adjusted for cardiac conditions and medications confirmed these findings, with minimal to no attenuation of HRs. Conclusion: New allopurinol use was independently associated with a lower risk of PAD in the elderly. Longer allopurinol use durations seemed more protective. Mechanisms of the protective effect need to be investigated in future studies.